Buku Visual Sebagai Media Pembelajaran Mata Kuliah Agama Islam untuk Mahasiswa Politeknik Elektronika Negeri Surabaya (PENS) - Citra Devi Murdaningtyas; Anggun Hapsari; Imamul Arifin (Universitas Negeri Padang, 2021)
The Islamic Religious Education course, which is then abbreviated as PAI, is a compulsory subject for Muslim students that must be implemented in every university in Indonesia. This is stated in Law No. 12 of 2012 Article 35 Paragraph 3 concerning Higher Education. In its implementation, Politeknik Elektronika Negeri Surabaya (PENS) has given these courses to students. This course aims to shape students into human beings who believe and fear Allah SWT. and have noble character. On the other hand, an understanding of the subject matter of PAI is very important in order to realize this main goal. Based on the results of research entitled Questionnaire for Islamic Religious Education Courses at PENS, it was stated that 75% of the 40 respondents found it difficult to learn and understand some chapters due to the lack of visualization of the material and too many terms that were difficult to understand or memorize. Another problem found through this research is that the intensity of respondents' reading activities is still relatively low. Therefore, this research is expected to be able to increase understanding related to PAI courses through reading activities for PENS students by contributing in the form of making visual books as interesting PAI learning medium.